Autoantibodies targeting interferons and GM-CSF are associated with adverse outcome risk, comorbidities, and pathogen in community-acquired pneumonia - Von Stemann, Jakob Hjorth; Dungu, Arnold Matovu; Laguarda, Maria Vispe; Ryrsø, Camilla Koch; Hegelund, Maria Hein; Faurholt-Jepsen, Daniel; Krogh-Madsen, Rikke; Hansen, Morten Bagge; Lindegaard, Birgitte; Ostrowski, Sisse Rye (Frontiers in Immunology, 2024)
Introduction Cytokine autoantibodies (c-aAb) have been associated with pulmonary diseases, including severe novel coronavirus disease 2019 (COVID-19) and pulmonary alveolar proteinosis. This study aimed to determine c-aAb association with community-acquired pneumonia (CAP) etiology (SARS-CoV-2, influenza, or bacteria) and c-aAb associations with CAP-related clinical outcomes and pulmonary comorbidities. Methods In a cohort of 665 patients hospitalized with CAP, c-aAb targeting interferon α (IFNα), IFNβ, IFNγ, interleukin-1α (IL-1α), IL-6, IL-10, and granulocyte-macrophage colony-stimulating factor (GM-CSF) were measured in plasma samples. Associations between c-aAb and baseline characteristics, pulmonary comorbidities, pathogen, intensive care unit (ICU) transferal, time to clinical stability, and mortality were estimated, with results stratified by sex. Results More men infected with SARS-CoV-2 were had high-titer type 1 IFN c-aAb compared to other pathogens. Among patients with CAP, asthma and bronchiectasis comorbidities were associated with high-titer GM-CSF c-aAb in men, and men with high-titer IFNβ c-aAb had increased odds for ICU transferal. High-titer IL-10 c-aAb were associated with faster clinical stability in women Conclusion In men with CAP, various c-aAb—including type 1 IFN and GM-CSF c-aAb—were associated with adverse clinical events and comorbidities, whereas c-aAb targeting an autoinflammatory cytokine were associated with a positive outcome in women. This suggests that the potentially immunomodulatory effects of c-aAb depend on pathogen, autoantibody specificity, comorbidity, and sex.